A quest for stakeholder synchronization in the CAR T-cell therapy supply chain - Holland, Shelby M.; Sohal, Amrik; Nand, Alka Ashwini; Hutmacher, Dietmar W. (Frontiers in Bioengineering and Biotechnology, 2024)
Advancements in cell therapy have the potential to improve healthcare accessibility for eligible patients. However, there are still challenges in scaling production and reducing costs. These challenges involve various stakeholders such as the manufacturing facility, third-party logistics (3PL) company, and medical center. Proposed solutions tend to focus on individual companies rather than addressing the interconnectedness of the supply chain's challenges. The challenges can be categorized as barriers from product characteristics, regulatory requirements, or lagging infrastructure. Each barrier affects multiple stakeholders, especially during a boundary event like product handover. Therefore, solutions that only consider the objectives of one stakeholder fail to address underlying problems. This review examines the interconnecting cell therapy supply chain challenges and how they affect the multiple stakeholders involved. The authors consider whether proposed solutions impact individual stakeholders or the entire supply chain and discuss the benefits of stakeholder coordination-focused solutions such as integrated technologies and information tracking. The review highlights how coordination efforts allow for the implementation of widely-supported cell therapy supply solutions such as decentralized manufacturing through stakeholder collaboration.